Glyptothorax viridis, a new species of catfish (Teleostei: Siluriformes: Sisoridae) from Manipur, India - Shangningam, Bungdon; Kosygin, Laishram (Zootaxa, 2023)
Glyptothorax viridis, new species, is described from the Dujang, a hill stream tributary of the Chakpi River, Chindwin drainage in Manipur, India. It is distinguished from its congeners by the following combination of characters: presence of plicae on paired fins; thoracic adhesive apparatus with a deep, cone-shaped median depression opening caudally; a slender pelvic fin reaching the anal fin, and tuberculated skin with three stripes on the body.